Lobomycosis: a therapeutic challenge - Marcelo Grossi Araújo; Nathalie Silva Cirilo; Soraya Neves Marques Barbosa dos Santos; Claudemir Roberto Aguilar; Antonio Carlos Martins Guedes (Anais Brasileiros de Dermatologia, 2018)
Abstract: Lobomycosis or lacaziosis is a chronic granulomatous fungal infection caused by Lacazia loboi. Most cases are restricted to tropical regions. Transmission is believed to occur through traumatic inoculation in the skin, mainly in exposed areas. It is characterized by keloid-like nodules. There are only a few hundred cases reported. The differential diagnoses include many skin conditions, and treatment is difficult. The reported case, initially diagnosed as keloid, proved to be refractory to surgical treatment alone. It was subsequently approached with extensive surgery, cryotherapy every three months and a combination of itraconazole and clofazimine for two years. No signs of clinical and histopathological activity were detected during follow-up.